The development of a food-group, tree classification method and its use in exploring dietary associations with metabolic dysfunction-associated Steatotic liver disease (MASLD) and other health-related outcomes in a UK population - Amina A. Alawadi; Amrita Vijay; Jane I. Grove; Moira A. Taylor; Guruprasad P. Aithal (Metabolism Open)
Background: Metabolic dysfunction-Associated Steatotic Liver Disease (MASLD) affects up to one in five people in the UK, with persistent overeating and a sedentary lifestyle being significant risk factors. Exploring dietary patterns at a food level is a novel approach to understand associations between diet and disease. Methods: This cross-sectional case-control study included 168 MASLD patients and 34 healthy controls from Nottingham (UK). Dietary data were collected using the EPIC-food frequency questionnaire. A food-group, tree classification method was developed which categorized 923 ingredients into three levels (main food group, sub-types, and cooking methods) and intakes were associated with clinical outcomes using logistic regression and degree of liver fibrosis using linear regression. Results: Significant associations were found for red meat intake with MASLD (OR [CI]: 1.013 [1.001–1.025]) and fibrosis (Beta [SE]: +0.048 [0.013]); intakes of nuts (OR [CI]: 0.951 [0.905–0.999]); and fish (OR [CI]: 0.985 [0.971–0.999]) with MASLD; “Cereals and cereals products”, “salt and gravy” and baked foods with fibrosis (Beta [SE]: +0.018 to +0.057 [0.005–0.23]); white and organ meat (Beta [SE]: −0.04 to −0.61 [0.015–0.249]); diet soda (OR [CI]: +0.01 [1–1.003]) and red meat intakes (OR [CI]:+0.002 [1.002–1.016]) with T2DM; wholegrain wheat, red meat, and semi-skimmed dairy intakes with hypercholesterolemia (ORs [CI]: −0.003 to −0.023 [1–1.043]); “herbs and spices” and wholegrain rice with hypercholesterolaemia (ORs [CI]: −0.08 to −0.98 [0.159–0.989); fresh herbs and boiled foods intakes with hypertension (ORs [CI]: −0.001 to −2.21 [0.013–1]). Conclusion: The study introduces a new food-group, tree classification method to characterise UK diet data and identify risk factors for MASLD, potentially informing the development of culturally applicable dietary guidelines designed to improve public health.